Improving Listening Comprehension Learning of the Seventh Grade Students through Digital Storytelling - Mohammada Umar Fakhrudin; Padmajati, Astri; Pranata, Sudadi (JELLT (Journal of English Language and Language Teaching), 2024)
Students’ low motivation in learning listening skill, inappropriate listening comprehension teaching, and insufficient facility and technological knowledge for online learning were found during preliminary research in seventh-grade students of a junior high school in Bantul. Action research was conducted with an aim to improve listening comprehension learning of grade seven students of the school through digital storytelling. Quantitative and qualitative data were collected during and after the research. It was found that students’ listening comprehension learning was improved based on the result of tests and assessment score in every meeting. Students’ mean score in pre-test improved from 44.44 to 64.44 in post-test with a medium score of N-gain (N-gain = 0.31). Other than that, the development was also observed during the process of learning in the classroom. Students’ mean score in weekly assessment improved from 60.56 in the first meeting to 65.56 and 76.11 in the second and third meeting. The reasons behind this improvement were analyzed through qualitative data, observation and interview with the collaborator. In the end, digital storytelling is able to improve students’ listening comprehension because it is a fun and interesting learning media for students and creative teaching media for teachers.